Preliminary interpretations from the 2015 Coompana aeromagnetic survey. Issue 1 (1st December 2016) - Wise, Tom; Pawley, Mark; Dutch, Rian
Abstract : The Coompana airborne survey is a large-scale pre-competitive aeromagnetic and radiometric survey in western South Australia flown in 2015. The survey was undertaken in order to provide greater geological controls on the basement geology in this area, which lies beneath the cover sequences of the Eucla, Bight, Denman and Officer Basins. This survey covers much of the South Australian part of the Coompana Province, which includes the Coompana Magnetic Anomaly. In this preliminary interpretation of the aeromagnetic survey, we have distinguished five basement domains based on the magnetic data and attempted to differentiate where domain boundaries are structural or intrusive. Integrating the aeromagnetic interpretation with existing drillhole and outcrop constraints suggests that the western part of South Australia had a long-lived, dynamic geological history with at least four major rock-forming events identified in the Coompana Province: c. 1610 Ma, c. 1500 Ma, c. 1180 Ma and c. 860 Ma. Detailed interpretation of the 200 m line-spaced infill region has enabled contact and relative age relationships of the intrusive bodies causing the Coompana Magnetic Anomaly. We suggest a multi-phase intrusive complex, with an early deep disc-like intrusion, followed by pipe-like satellite bodies intruding higher into the crust. The relative age of this intrusive complex is interpreted to be between c. 1120 Ma and c. 860 Ma.